Principles and Applications of Generative and Cognitive Grammar: A Systematic Literature Riview - Syalshabillah, Aura; Kasriyati, Destina; Andriani, Refika (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This study investigates the principles and applications of generative and cognitive grammar, focusing on their influence on language acquisition, literacy development, and second language learning. Spanning from 2020 to 2024, Databases such as Google Scholar and Crossref were used for the initial search, utilizing tools like Zotero and Publish or Perish. Keywords such as